Some Enzymatic and Non-enzymatic Antioxidants Response under Nickel and Lead Stress for Some Fabaceae Trees - Khudhur, Sargul A.; Albarzinji , lkbal M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
This study investigates the effects of soil contamination by nickel and lead on some enzymatic and non-enzymatic antioxidants in addition to the nitrate reductase (NR) enzyme activity for Gleditsia triacanthos, Leucaena leucocephala, and Robinia pseudoacacia plant species. The results of this study show a significant increase in peroxidase enzyme activity and a significant decrease in catalase enzyme activity, proline, total carotenoids, and total carbohydrate content of leaves of the three species with increasing the concentration of Ni and Pb except for the total carbohydrate, which increased only for L. leucocephala species. Each NR enzyme activity and ascorbic acid content are increased significantly with increasing the concentration of Ni and Pb for G. triacanthos, L. leucocephala, and on the contrary, they decreased significantly for R. pseudoacacia species. From the result, we can conclude a general increase or decrease in leaves content of some antioxidants content for all the species, whereas there is some peculiarity according to the plant species regarding other contents, which in turn reflects different mechanisms of these species to tolerant heavy metal stress